Feasibility Study of River Bank Filtration (RBF) at Sg. Kampar, Perak Using Numerical Modelling Technology (Visual Modflow) - Tajul Baharuddin, Mohamad Faizal; Yusoff, Nor Azizi; Embong, Zaidi; Lim, Alvin John Meng Siang (Penerbit UTHM, 2020)
Water demand around a world was increased due to growth of population, economy and urbanization [1]. Malaysia as a developing country is not exception to have a problem in order to cater an adequate water demand. According to populations statistic in Malaysia [2], the total population is about 32.0 million peoples in year 2017. In year 2016, the total water supply was increased about 97.7 % compared to year 2015. The facts showed that increased of water demand in line with the increase of population [2].